Lean Transformation Success: The Role of Management and Employee Engagement - Ivona Jovanović; Milena Gatić; Dragana Stojanović; Dušan Gošnik (Management)
The purpose of this research is to compare the engagements of employees and management throughout Lean transformation, which could enhance the Lean transformation success and encourage better fulfilment of goals. Based on the role of Lean and the importance of the decisions of management within a company, we wanted to identify which management and employee engagements are efficient and does their common influence can lead to a successful Lean transformation. Data was collected through an online survey, in which participants expressed their opinions on various aspects of Lean transformation in the company. The paper provides a comparative discussion of engagements, which could be useful for improving a company’s waste elimination, cost reduction, improving capabilities, increasing competitive advantage, financial and operational performance improvement. It gives practitioners guidelines on building a corporate culture where management and employees’ roles and involvements are directed towards achieving successful Lean transformation. Research Question: This study investigates which management and employee engagements enhance the fulfilment of Lean transformation goals and whether there is any difference in opinion among management and employees about Lean transformation success. Motivation: Our motivation was to explore different stakeholder roles within the company for Lean transformation. Idea: The main idea of this study was to examine the role of Lean from two perspectives, based on the level of engagement and role in the company – management and employee roles, and how they influence the company’s success. Data: An online survey was conducted, where the respondents pointed to various aspects of the company, such as company size, industry they operate in, ownership structure, etc. Data processing was carried out in the SPSS 25 package on 82 responses. Tools: As the initial step of the research, using Cronbach's alpha, it was concluded that obtained set of items in the group are closely related and measure a particular aspect. Mann-Whitney U test and Spearman-rho correlation test were used for the data analysis. Findings: The findings present a comparison of engagements and recommendations for engagements to follow in order for the company to be more successful in Lean transformation. Contribution: This research can help in reducing the research gap on the lack of comparisons of the engagement in these stakeholder roles. It provides practitioners with guidance on what steps they should take to be more successful in Lean transformation so that they can focus more on overcoming them and less on identifying them.